THE ROLE OF WOMEN’S SOCIAL ACTIVITY IN THE LIFE OF SOCIETY: A PEDAGOGICAL ANALYSIS (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the role of women’s social activity in the life of society from a pedagogical perspective. In the contemporary world, women’s participation in education, family upbringing, professional activity, civic initiatives, leadership, social protection and community development is considered an important indicator of social progress. The article emphasizes that women’s social activity is not limited to economic or political participation; it also includes moral education, social responsibility, cultural continuity, human capital development and the formation of democratic values among the younger generation. The purpose of the study is to reveal the pedagogical significance of women’s social activity and to identify the educational mechanisms that strengthen women’s participation in society. The research is based on theoretical analysis, comparative approach, content analysis of international documents and pedagogical interpretation. The results show that women’s active participation contributes to the development of social stability, civic consciousness, family culture, educational quality and inclusive social relations. The article concludes that gender-sensitive education, lifelong learning, leadership training and the elimination of stereotypes are essential pedagogical tools for increasing women’s social activity.